UPAYA MENINGKATKAN KEBERHASILAN TRUST DAN REPUTASI BISNIS MELALUI CONSUMER-TO-CONSUMER (C2C) E-COMMERCE - UTAMA, ALOYSIUS PANJI (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Along with technological advances, more and more people are interested and eventually using technology for the benefit of such everyday activities, such as purchase, sale, transfer, or exchange of products, services, or information via computer networks, including internet. C2C (Customer to Customer) is a business model where consumers act as sellers or service providers that provide goods or services to other customers. The C2C business is conducted to meet the sellers and buyers so they can connect directly without going through the intermediaries. Therefore, the internet is the most suitable place for a business model like this. In this case, everyone can access easily use it anywhere and anytime and not limited by space and time. However, the necessary requirements that could underlie the realization of C2C E-Commerce are trust and reputation. Therefore, consumers who want to utilize various forms of social networking for the benefit of doing business (E-Commerce) must be able to build trust and establish a reputation. To support the successful of C2C practice, there are a number of ways that can be done by the seller, which are: (1) build trust among consumers, (2) establish a reputation to convince consumers, (3) build a blog to reassure consumers, (4) establish cooperation with the firm or a public figure as a form of moral assurance, and (5) required the establishment of clear legal rules.